Analysis of the Impact of Open-Source Software on Reducing the Use of Pirated Software by Educators - Basrul Abdul Majid; Haya Fadiya; Khairan Ar (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2024)
One of the motivations for using pirated software can be caused by the need for more awareness of the importance of respecting the intellectual property rights of the software. Even in the college environment, there is software piracy. Educators and students freely use illegal software. While mean it is an environment for intellectuals and academics to gather, a place to study up to the highest level of education. This area should become an example for the surrounding community in respecting the copyrights of other things. One alternative to reduce the emergence of acts of using pirated software is to use open-source software. It is a free software version to use at will without pirating it. In this study, we want to know the influence of motivation in using pirated through the presence of open-source software. The data taken is among educators, as many as 86 randomly selected respondents. The data is processed quantitatively with the regression method. The results showed that the motivational factor in pirated software did not tremendously affect the factor of open-source software. It is only 14%, and the rest had no effect.